Analisis manajemen risiko dalam prosedur pembiayaan gadai emas - Izzudin, Dani (Maliki Interdisciplinary Journal, 2025)
This study discusses the analysis of risk management in the gold pawn financing procedure, which is one of the collateral-based financial services. Gold pawn is a popular financing alternative in the community because of its fast process, relatively easy requirements, and stable collateral value. However, in its implementation, there are various risks that need to be managed properly by financing institutions, including credit risk, operational risk, legal risk, and market risk. Risk management in the context of gold pawn financing includes identification, evaluation, and control of risks that may arise during the loan granting and repayment process. Common procedures include assessing the authenticity and value of gold, analyzing customer eligibility, and preparing internal policies that regulate loan limits and terms. In addition, a good monitoring and documentation system is also needed to prevent potential misuse or fraud. Financing institutions need to have a structured and integrated risk mitigation strategy, such as developing information technology to monitor transactions in real time, training human resources, and strengthening internal regulations. Effective risk management can increase public trust in gold pawn services and maintain the operational stability of the institution. This study concludes that a systematic and comprehensive risk management approach is essential to minimize potential losses and support the sustainability of gold pawn financing services amidst economic dynamics and changes in consumer behavior.